Advanced Cardiac Life Support Checklists for Simulation-Based Education - Diane Wayne; John Butter; Aashish Didwania; Viva Siddall; William McGaghie (Association of American Medical Colleges, 2009)
Abstract Introduction Since 2003, we have used evidence-based checklists to score the performance of internal medicine residents in advanced cardiac life support (ACLS) protocols. Using the American Heart Association textbook, we created these clinical scenarios and procedural checklists for six common ACLS conditions. The conditions are 1) ventricular fibrillation, 2) asystole, 3) pulseless electrical activity, 4) narrow complex tachycardia, 5) symptomatic bradycardia, and 6) ventricular tachycardia. Methods The checklists are used in a mastery learning program to obtain pretest and posttest scores. The curriculum contains the opportunity for deliberate practice and feedback using a full-size human patient simulator. At posttest, the residents are expected to meet or exceed a minimum passing standard set by an expert panel. Those who do not meet the standard are referred back to the simulation lab for additional practice and feedback. Results Using the simulation-based education described above, we demonstrated a 40% increase in adherence to American Heart Association protocols in simulated ACLS scenarios after training. We also showed that skills were retained over a 14-month period. A chart review showed that improvement also carried over to the clinical environment as residents with simulator training were significantly more adherent to American Heart Association guidelines in actual ACLS patient care than residents who did not receive simulator training. Discussion As described above, the checklists have been used in research studies that have shown improved ACLS performance in the simulated environment and in actual patient care. As ACLS proficiency is required by the American Board of Internal Medicine, we believe our resource would be of use to program directors throughout the United States. The protocols were developed for use with a human patient simulator that displays blood pressure, pulse, and a realistic response to medication. The simulator accommodates a defibrillator and pacemaker. Thus, compatible equipment would be needed for maximal benefit of the checklists. However, as simulators have become widespread, we believe many institutions could use these algorithms to teach and assess residents in ACLS.